2020
DOI: 10.1177/0969733020901830
|View full text |Cite
|
Sign up to set email alerts
|

Perception of care quality and ethical sensitivity in surgical nurses

Abstract: Background: It is stated that high ethical sensitivity positively affects the quality of nursing care. However, the relationship between nursing care quality and ethical sensitivity has not been clearly demonstrated in researches. Aim: This study was carried out to determine the relationship between surgical nurses’ care behaviors and their ethical sensitivity. Method: The sample of this cross-sectional, descriptive-correlational study consists of 308 nurses who worked at the surgical departments in four Turki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 19 publications
2
28
1
2
Order By: Relevance
“…Similar to previous studies [ 56 , 57 ], our study revealed that the perceived hospital ethical climate, ethical sensitivity, and self-evaluated care quality were positively correlated with each other and that ethical sensitivity partly mediated the relationship between hospital ethical climate and self-evaluated care quality. Nurses played a crucial role in the treatment and care of COVID-19 patients, and ethical sensitivity was essential for nurses to provide high-quality care.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to previous studies [ 56 , 57 ], our study revealed that the perceived hospital ethical climate, ethical sensitivity, and self-evaluated care quality were positively correlated with each other and that ethical sensitivity partly mediated the relationship between hospital ethical climate and self-evaluated care quality. Nurses played a crucial role in the treatment and care of COVID-19 patients, and ethical sensitivity was essential for nurses to provide high-quality care.…”
Section: Discussionsupporting
confidence: 89%
“…The findings reveal that nurses experienced an inevitable sense of a loss of control when facing the suffering of patients combined with the perceived risks in contaminated environments, though having a sense of control is vital for nurses to resist distress and anxiety ( Gallagher et al, 2014 , Taylor et al, 2020 ). Evidence indicates that healthcare professionals frequently met ethical challenges in difficult work conditions ( Mert et al, 2020 , Cerit and Dinç, 2013 , Amiri et al, 2019 ). Insufficient knowledge and resources, uncertainty with duties and procedures, and communication problems are the major causes of ethical issues and moral distress felt by nurses, and it is consistently noted that nurses are unable to provide adequate care when facing these challenges ( Dehghani et al, 2015 , Mert et al, 2021 , Silverman et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 The physicians and nurses often have ethical problems due to working in units like surgical units where there are complex structures, circulation, and use of technology is high, surgical patients have a high risk of injury, infection, and exposure to dangerous substances, unexpected, life-threatening, and rapid decision-making situations often develop. 2,3…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic period in which ethical issues may be encountered requires the development of ethical sensitivities of physicians and nurses to make ethical decisions. 3,6,20 High ethical sensitivity not only contributes to professionalization but also directly affects the quality of treatment and care for patients. 3,21 In professional healthcare practices, identifying the attitudes and behaviors of surgical physicians and nurses on ethical sensitivity, which is one of the significant components of qualified treatment and care, can contribute to taking the necessary precautions by identifying the deficiencies and errors in this regard and can also be beneficial in raising the awareness level of health professionals and the treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation